2004
DOI: 10.1073/pnas.0402312101
|View full text |Cite
|
Sign up to set email alerts
|

Brain renin-angiotensin system blockade by systemically active aminopeptidase A inhibitors: A potential treatment of salt-dependent hypertension

Abstract: The hyperactivity of the brain renin-angiotensin system (RAS) has been implicated in the development and maintenance of hypertension in several types of experimental and genetic hypertension animal models. We previously reported that in the murine brain, aminopeptidase A (APA) is involved in the conversion of angiotensin II (AngII) to AngIII and that AngIII is one of the main effector peptides of the brain RAS in the control of vasopressin release. Here we report that brain AngIII exerts a tonic stimulatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
131
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 45 publications
(40 reference statements)
7
131
0
2
Order By: Relevance
“…Together, these data demonstrated that Ang III, generated by APA, is one of the main effector peptides of the brain RAS, exerting a tonic stimulatory control over BP in alert hypertensive rats. 21,24 This conclusion was confirmed by Wright et al 26 using the same inhibitors. The interpretation of these results has been challenged recently.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Together, these data demonstrated that Ang III, generated by APA, is one of the main effector peptides of the brain RAS, exerting a tonic stimulatory control over BP in alert hypertensive rats. 21,24 This conclusion was confirmed by Wright et al 26 using the same inhibitors. The interpretation of these results has been challenged recently.…”
supporting
confidence: 78%
“…More interestingly, ICV injection, but not IV injection, of EC33 alone caused a dose-dependent decrease in BP in alert spontaneously hypertensive rats, a model of essential hypertension sensitive to RAS blockers, and DOCA-salt rats, a salt-and volume-dependent model of hypertension 22,23 resistant to systemic RAS blockers. 21,24,25 This suggests that the blockade of the formation of brain but not systemic Ang III is responsible for the decrease in BP. This conclusion was strengthened by the fact that the selective APN inhibitor PC18, administered alone via the ICV route, increased BP.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, high blood pressure caused by hyperactive brain RAAS in the DOCA-salt sensitive rat can be reduced for up to 24 hours by a selective inhibitor of APA that is able to transgress the blood-brain barrier (Fournie-Zaluski, et al, 2004). Thus, the APA protein has been implicated in proteinuria and salt-induced hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…3,4 Ang III, also called Ang- (2)(3)(4)(5)(6)(7)(8), is generated from Ang II by aminopeptidase A (APA), which cleaves the Asp 1 -Arg 2 bond in Ang II. Persuasive evidence have been presented in support of this "Ang III hypothesis": (1) Ang III, when centrally administrated, enhances BP; stimulates vasopressin release, thirst, and sodium appetite; and decreases baroreceptor reflex function 3,5,6 ; (2) Ang III displays comparable affinity to Ang II for the type 1 Ang II receptor 3 ; (3) specific inhibitors of APA that block the conversion of Ang III from Ang II attenuate central Ang II actions 4 (eg, central treatment with EC33, an APA inhibitor, attenuates ICV-administrated Ang II effects on BP; in addition, ICV injection of this inhibitor decreases brain Ang III formation) 7,8 ; and (4) APA-resistant analogs of Ang II fail to influence central actions. 4 However, this Ang III hypothesis is not without its critics.…”
mentioning
confidence: 99%